Impact and synergies of GIM error estimates on the VTEC interpolation and single-frequency PPP at low latitude region - Jerez, Gabriel O. [UNESP]; Hernández-Pajares, Manuel; Goss, Andreas; da Silva, Crislaine Menezes [UNESP]; Alves, Daniele B. M. [UNESP]; Monico, João F. G. [UNESP] (Springer Nature, 2022)
The vertical total electron content (VTEC) is one of the key quantities to describe variations of the ionosphere and can be provided to users to correct the ionospheric disturbances for GNSS (Global Navigation Satellite System) positioning. The VTEC values and the corresponding standard deviations are routinely provided in the so-called Global Ionosphere Maps (GIM), with a typical time resolution of 2 h (and up to 15 min) on regular grids with 2.5º resolution in latitude and 5º resolution in longitude. To determine the ionospheric corrections from the GIMs for positioning applications, an interpolation has to be applied to the VTEC grid values, which generally degenerates the final VTEC accuracy. In this context, the typically applied bi-linear interpolation of the VTEC values is calculated by introducing a new weighting scheme by means of the standard deviation maps in the ionospheric domain. In the sequel, the impact of the use of the VTEC uncertainties for the interpolation procedure is applied to the GIMs of different centers and assessed in the ionospheric and in the positioning domain. For the assessment of the GIM in the ionospheric domain, the VTEC values calculated are compared with VTEC directly obtained from the given GIM, i.e., without interpolation. In the positioning domain, the impact of the VTEC uncertainties is analyzed by means of single-frequency precise point positioning (PPP), considering four Brazilian stations in challenging regions. The use of the standard deviation values in positioning provides a significant improvement in periods of high solar flux, especially for stations in the region under more intense ionospheric effect (mean rates of improvements up to 47%).
Keywords: Equatorial region; Global ionospheric maps; GNSS positioning; Ionosphere; PPP